Synthesis and Characterization of a New Keggin-Type Polyoxoniobate for Application as Anodes in Sodium-ion Batteries (SIBs) - Matsushita, Alan Fernando Yoshiaki; Nascimento , Josias do Rocio Vitor do; Leite, João Manoel de Aguiar; Garcia, Jarem Raul (Orbital: The Electronic Journal of Chemistry, 2025)
In the pursuit of sustainable energy solutions and advancements in energy storage technology, this research focuses on the synthesis, characterization, and electrochemical evaluation of a Keggin-Type polyoxoniobate compound for potential application in sodium-ion batteries (SIBs). While lithium-ion batteries have been the standard, concerns about lithium availability and environmental issues have prompted the exploration of alternative materials for SIBs. Polyoxoniobates, a subclass of polyoxometalates, have unique properties that make them promising candidates for the development of high-performance SIBs. This study delves into the relatively uncharted territory of polyoxoniobates in SIBs. The research investigates the adaptation of polyoxoniobate structures to enhance their electrochemical properties, the understanding of sodium ion storage mechanisms, and comprehensive characterization. A specific Keggin-Type polyoxoniobate compound is synthesized and examined for its potential as an electrode material for SIBs. The structural analysis confirms the successful synthesis of the compound, with X-ray diffraction patterns, Raman spectroscopy, and FTIR spectra demonstrating its purity and integrity. Scanning electron microscopy reveals the unique morphology of the composite material, indicating interactions between graphene oxide (GO) and polyoxoniobates. Elemental analysis further confirms the composition of the composite material, aligning with the expected stoichiometry. Electrochemical characterization using various techniques, including cyclic voltammetry, chronopotentiometry charge/discharge, and electrochemical impedance spectroscopy, provides insights into the electrochemical behavior of the synthesized material. These findings contribute to the understanding of structure-activity relationships in polyoxoniobates and their potential as crucial components in future SIBs.